2022
DOI: 10.3389/fmed.2022.959010
|View full text |Cite
|
Sign up to set email alerts
|

Identification of diagnostic gene biomarkers related to immune infiltration in patients with idiopathic pulmonary fibrosis based on bioinformatics strategies

Abstract: ObjectiveThe study aims to identify potential diagnostic markers of idiopathic pulmonary fibrosis (IPF) and analyze the significance of immune cell infiltration in this pathology.Materials and methodsDownload two publicly available gene expression profiles (GSE10667 and GSE24206 datasets) from the GEO database including 48 Idiopathic pulmonary fibrosis (IPF) samples and 21 human control samples and select for distinctly expressed genes (DEG) from them. Lasso regression model and support vector machine recursiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 51 publications
1
6
0
Order By: Relevance
“…This methodology aligns with the research conducted by Dai et al. ( 15 ), but extends their work by providing further in-depth MR causal validation for the identified DEGs.…”
Section: Discussionsupporting
confidence: 75%
“…This methodology aligns with the research conducted by Dai et al. ( 15 ), but extends their work by providing further in-depth MR causal validation for the identified DEGs.…”
Section: Discussionsupporting
confidence: 75%
“…We found very distinct differences between them. Though IL-8 treated samples resulted in downregulated genes involved in fibrotic events, including extracellular matrix organizers ( COL4A1 , COL10A1 ) (37, 38), IL11 (39, 40). However, it can enhance canonical signaling drives fibrotic programs, as evidenced by upregulated TGFβR3 and SMAD3 that are essential in fibrosis (41, 42) (Supplemental Figure 6, D-F).…”
Section: Resultsmentioning
confidence: 99%
“…This model has made significant progress compared to other models in previous studies 37 . This progress is primarily reflected in the use of fewer feature variables, the validation of the model using a large-scale dataset, and its strong predictive performance.…”
Section: Discussionmentioning
confidence: 97%
“…Insulin-like growth factors (IGFs) and their binding proteins (IGFBPs) play a critical role in pulmonary fibrosis development and progression 37 . It has previously been shown that IGFBP2 and IGF-like family member 2 (IGFL2) are upregulated in SSc-PF and IPF 38 .…”
Section: Discussionmentioning
confidence: 99%